PECULIARITIES OF HOMOLOGOUS AND NONHOMOLOGOUS PAIRING OF POLYTENE CHROMOSOMES IN THE INBRED LINES AND HYBRIDS OF DROSOPHILA - Shakina, L.; Strashnyuk, V.; Shakhbazov, V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2005)
Peculiarities of homologous and nonhomologous pairing of polytene chromosomes in the inbred lines and hybrids F1 of drosophila were studied. The data received testify that frequency of ectopic pairing of sites 100 F and 92 EF in chromosome 3R and frequency of asynapsis in chromosome 3R depend on a genotype. The influence of the ectopic contact on the frequency of 3R-chromosome homologs asynapsis and puffing activity in the locus 93D is shown. The probable role of the cell nucleus chromosome spatial organization in the mechanism of heterosis is supposed.